Clitoria ternatea L. extract cream 5% inhibited the increase of MMP-1 levels and decrease of collagen amount in wistar rats (Rattus norvegicus) dermic skin exposed to ultraviolet B - Ayunda Tamara Barito Saritani; Anak Agung Gde Putra Wiraguna; Luh Putu Iin Indrayani Maker (Indoscholar, 2021)
Background: Photoaging increases MMP-1 and damage collagen by forming ROS. The antioxidant compounds in Clitoria ternatea L. have been studied to lower ROS, thus inhibiting the emergence of MMP-1 and preserving the collagen. The study initiated to analyze the Clitoria ternatea L. extract cream 5% effect on inhibiting MMP-1 increase and collagen decrease in female Wistar rat's skin exposed to UV-B. Methods: A randomized post-test-only control group design was conducted on 30 female Wistar rats, aged 8-10 weeks old with 130-150 grams bodyweight. They were assigned to three groups: the untreated group, placebo group, and the Clitoria ternatea L. extract cream 5% group. The last two groups were exposed to UV-B. After four weeks their skin was examined for MMP-1 levels using ELISA and collagen amount using Picro Sirius Red staining. Results: A comparative analysis showed that the lowest mean levels of MMP-1 was seen in the untreated group (4.64 ± 0.14 ng/ml), followed by the Clitoria ternatea L. extract cream group 5% (5.54 ± 0.21 ng/ml) and placebo group (8.68 ± 0.78 ng/ml). The highest mean of collagen amount was seen in the Clitoria ternatea L. extract cream group 5% (76.12 ± 5.09 %pixel), followed by the untreated group (69.38 ± 3.96 %pixel) and placebo group (30.31±8.06 %pixel). The comparative analysis shows a significant difference between groups (p < 0.05). Conclusion: The Clitoria ternatea L. extract cream 5% has proven to inhibited the increase of MMP-1 levels and decrease of collagen amount in Wistar rats skin exposed to UV-B.